2017
DOI: 10.1200/jop.2016.016857
|View full text |Cite
|
Sign up to set email alerts
|

Promise of Wearable Physical Activity Monitors in Oncology Practice

Abstract: Commercially available physical activity monitors provide clinicians an opportunity to obtain oncology patient health measures to an unprecedented degree. These devices can provide objective and quantifiable measures of physical activity, which are not subject to errors or bias of self-reporting or shorter duration of formal testing. Prior work on so-called quantified-self data was based on older-generation, research-grade accelerometers, which laid the foundation for consumer-based physical activity monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 65 publications
1
61
0
Order By: Relevance
“…Since previous research has shown that women are more likely to be ruminators [30] and are influenced by peer support, health care providers may want to provide female cancer survivors with motivational support and symptom management strategies to help promote PA after cancer. Female cancer survivors may respond better to nurse-led, group-based, or mobile text-based PA interventions than their male counterparts [31]. Additionally, emerging research is showing that wearable PA monitors have potential to serve as a motivational tool and their use has been found to improve PA levels among cancer survivors [3134].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous research has shown that women are more likely to be ruminators [30] and are influenced by peer support, health care providers may want to provide female cancer survivors with motivational support and symptom management strategies to help promote PA after cancer. Female cancer survivors may respond better to nurse-led, group-based, or mobile text-based PA interventions than their male counterparts [31]. Additionally, emerging research is showing that wearable PA monitors have potential to serve as a motivational tool and their use has been found to improve PA levels among cancer survivors [3134].…”
Section: Discussionmentioning
confidence: 99%
“…Female cancer survivors may respond better to nurse-led, group-based, or mobile text-based PA interventions than their male counterparts [31]. Additionally, emerging research is showing that wearable PA monitors have potential to serve as a motivational tool and their use has been found to improve PA levels among cancer survivors [3134]. Clinical care teams may want to encourage sedentary female survivors to use PA monitors as a way to self-monitor and track PA levels throughout the day.…”
Section: Discussionmentioning
confidence: 99%
“…As for the impact at point of care, a recent study by Birkeland et al [13] illustrated that wearable device-determined step count was able to determine treatment effect in patients with coronary microvascular dysfunction. The specific role of activity monitors at the point of clinical care has been reported in oncology, COPD, and other chronic medical conditions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that activity monitors can detect differences in mobility between ostensibly healthy elderly or adult populations relative to elderly with reduced mobility [6]. With the advancement in wearable technology, devices can passively and objectively measure high-resolution mobility data, as opposed to subjective questionnaires and observations which are subject to bias of self-reporting or shorter duration of formal testing [7,8]. This has led to increasing research on consumer activity monitors.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical applicability of perioperative activity monitoring remains unknown at this early stage of research [36]. Nonetheless, commercial activity monitors for surgical patients could yield potentially important information at minimal cost and no increased risk [20,37].…”
Section: Commentmentioning
confidence: 99%